Big bear, little bear - Bedford, David, 1969-; Chapman, Jane, 1970- (London : Little Tiger Press, 2011)
Mother Bear shows Little Bear what it is like to be big when he wishes that he could grow up faster, but he decides that being small is fun, too. Features textured pages.
Originally published: Great Britain : Little Tiger Press, 2001.
2.2
K-3.
K-3
Keywords: Bears -- Fiction; Mothers and sons -- Fiction; Polar bears -- Fiction; Textured books; Bears -- Fiction; Mother-son relationship -- Fiction; Polar bears -- Fiction; Toy and movable books